Tufted Angioma in Children: Report of Two Cases and a Review of the Literature - Alessandra Dutra da Silva; Grasieli de Oliveira Ramos; Rita Fabiane Teixeira Gomes; Marco Antônio Trevizani Martins; Marcelo Lazzaron Lamers; Manoel Santa’Ana Filho; Pantelis Varvaki Rados; Laura de Campos Hildebrand; Fernanda Visioli (Case Reports in Dentistry)
Tufted angioma (TA) is a benign vascular tumor with endothelial origin. It is extremely rare in oral mucosa; only seven cases have been reported in the literature so far. Here, we describe two cases of tufted angioma observed in children and we also present a review of the literature about this pathology, concerning the differential diagnosis and management of this lesion in children.